Promessas de campanha eleitoral na agenda de governo em Moçambique: uma contribuição para a análise na gestão governamental (2015-2019) - Matavel, Princidónio Abrão (2022)
The research that gave rise to this thesis aims to analyze the election campaign promises and their fulfilment in the area of education, in public primary and secondary education in Mozambique, in the governing term of President Filipe Jacinto Nyusi, in his first governmental term 2015 to 2019. We opted for this study as a research strategy because we consider it appropriate to analyse this complex political phenomenon for the African reality, specifically Mozambican, and for providing the understanding of holistic peculiarities of the researched fact. The research was fundamentally based on a qualitative approach. The verification of the fulfillment of the promises was through the survey and analysis of data from the National Institute of Statistics (INE), the Ministry of Education and Human Development (MINEDH) of the Economic and Social Plans and their respective State Budgets corresponding to the five-year period in allusion; and textual documents Political and government programs, government legislation, reports and strategic plans of education in primary and secondary public education linked to the MINEDH. The theoretical basis that supported this thesis was Downs' Theory of Mandate (1957), which was considered the most convenient for verifying the fulfilment of electoral campaign promises in the area of education in public primary and secondary education. From the cross-referencing of the data obtained from the analysis of the research, the most significant results of the thesis conclude that despite the skepticism of most Mozambican citizens, the government administration of President Filipe Jacinto Nyusi in his first term of office, at the level of education, fulfilled most of the promises, in a percentage above 70% of the indicators analysed, in a context of major financial constraints. This means that despite the degradation of the entire national education system in Mozambique, there was some responsiveness and, consequently, a correspondence between the electoral promises and government action.